Foreign trade in the economic development of small nations : the case of Ecuador - Gibson, Charles R (New York : Praeger publishers, 1971)
This study attempts to relates international trade theory and economic development theory in the context of a small developing nation, Ecuador.
Includes bibliography
ijb, 15/01/2019
Loans
Keywords: Commerce; Economic History; Ecuador